PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMP MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING - Mahmuzah, Rifaatul; Sinaga, Nurul Afni; Ainun, Nur (Mandalika Mathematics and Educations Journal, 2024)
Mathematics is a branch of science that contributes to changing a person's way of thinking and reasoning, making reasoning abilities crucial to enhance. Teachers, as educators, must choose the right approach to improve students' reasoning skills. Contextual Teaching and Learning (CTL) is one approach to learning that is expected to enhance students' mathematical reasoning abilities. The research aims to examine the improvement in students' mathematical reasoning abilities taught using the Contextual Teaching and Learning (CTL) approach compared to those taught using conventional learning methods. This research is an experimental study with a Pretest-Posttest Control Group Design. The population in the study consists of all eighth-grade students at SMP Negeri 1 Darul Imarah, Aceh Besar. The research sample comprises two classes: class VIII2 as the experimental group and class VII3 as the control group, selected randomly. The instrument used to collect research data is a mathematical reasoning ability test, while the statistical test used to analyze the improvement in mathematical reasoning ability is a parametric test, namely the independent sample t-test. The results of the research indicate that the improvement in students' mathematical reasoning abilities who received instruction using the CTL approach is better compared to those who received instruction using conventional methods.